Aspidistra stenophylla (Asparagaceae), a new species from Guangxi, China - Hu, Ren-Chuan; Shen, Xiao-Lin; Liu, Jing; Lin, Chun-Rui (Phytotaxa, 2014)
The genus Aspidistra Ker-Gawler (1822: t. 628) presently includes about 120 species have been discovered, mainly distributed in China and Vietnam, but also in Japan, Thailand, Laos and India (Liang & Tamura 2000, Li 2004, Tillich 2005, 2008, Tillich et al. 2007, 2013, Hou et al. 2009, Lin et al. 2009, 2011, 2013, Meng et al. 2014, Vislobokov et al. 2014). In May 2012, during the course of investigating limestone plants in southwestern Guangxi, China, near the border to northern Vietnam, we collected an unusual Aspidistra specimen with urceolate perigone in Jingxi County. It was transplanted to the Guilin Botanical Garden for cultivation, and flowered regularly in the next year. Compared with other species of Aspidistra, it was recognized as an undescribed species, which we describe below.